Some morphological and physiological characteristics of Aloe vera under the treatment of urban and industrial wastewater - Sareh Ebrahimi Nokande; Seyed Mehdi Razavi; Mansour Afshar Mohammadian (Zīst/shināsī-i Giyāhī-i Īrān, 2022)
AbstractOne of the environmental problems is soil pollution with heavy metals from urban and industrial wastewater, and the treatment of these pollutants by plants is a cost-effective and environmentally friendly method. In this study, an experiment was conducted to evaluate the phytoremediation rate of Aloe vera in terms of metal accumulation index (zinc, chromium, lead, copper, manganese, nickel, magnesium, cadmium, mercury) and its morphological characteristics under two types of urban and industrial wastewater treatment. The design was completely randomized with three replications. The results showed that urban and industrial wastewater treatments caused significant changes (P≤0.05) in all examined parameters including leaf fresh weight, leaf dry weight, relative leaf water content, leaf length, leaf gel weight, the ratio of gel to leaf, root fresh weight, fresh plant weight, total biomass, root length, plant height, number of ramets, ramets height, ramets weight and root tolerance index in Aloe vera. The highest index of metal accumulation was observed in plants treated by urban wastewater and all the mentioned parameters showed a more significant decrease by treatment of urban wastewater than industrial wastewater. In the industrial wastewater treatment, all parameters decreased, but the average number of ramets increased compared to the control. In general, based on the parameters studied in this study, it can be said that the Aloe vera plant had better performance in soils containing industrial wastewater than in soils containing urban wastewater. IntroductionOne of the environmental problems is soil pollution with heavy metals from urban and industrial wastewater. Human activities such as the disposal of household waste and industrial activities mainly import heavy metals into the soil (European Commission, 2013; USEPA, 2021). Heavy metal pollution of soil can harm human life and the ecosystem through direct intake or entering the food chain (soil-plant-human or soil-plant-animal-human) (European Commission, 2013). Phytoremediation is a biological and cost-effective method to remove or reduce environmental pollutants. Some plants can remove, stabilize or transfer contaminants of soil or groundwater (Gajic and Pavlovic, 2018). Therefore, choosing a suitable plant for phytoremediation can be a crucial step in eliminating pollution based on region and type of pollution and expansion of urban wastewater.The province of Guilan, located in the north of Iran, has a humid subtropical climate and is a fertile province in terms of agriculture. The increased urban population in this province can cause pollution transfer into the river or land fields. This problem threatens the agricultural products of Guilan and causes a critical challenge. It seems that the cultivation of plants with high phytoremediation ability and the creation of a green belt in the landfill site of urban and industrial wastewaters is the most feasible and low-cost method to decrease the risk of soil and water pollution. In this study, we examined the ability of Aloe vera for phytoremediation of urban and industrial wastewater (UWW and IWW) and the possible alterations of, its morphological and physiological characteristics under wastewater pollution. Materials and Methods For this study, Aloe vera plants gathered from the local nursery were planted in the pots containing 11 kilos of soil suitable for A. vera cultivation. After a month of transferring the plants to the pots and adapting them to the new conditions, they were divided into three groups. Each group was irrigated for 14 months (every twice a week) with 300 mL of one type of solutions consideredas treatments for this experiment, including urban water (drinking water), UWW collected from the landfill site of Saravan, and IWW collected from the paper factory. Moreover, pots without plants were irrigated like pots with plants to determine the amounts of heavy metals (zinc, chromium, lead, copper, manganese, nickel and magnesium) after wastewater addition to the soil and compare it with maximum standard levels, pots with plants.Soil samples were homogenized and dried in an oven at 30°C for 24h and the concentration of heavy metals was determined. The relative water content (RWC) of leaves was measured before harvesting plants (Barrs and Weatherley, 1962). After harvesting the whole plants, leaf fresh weight, leaf length, leaf gel weight, ratio gel to leaf, root fresh weight, plant fresh weight, root length, plant height, number of ramets, ramets height, ramets weight, and tolerance index were measured. Leaf dry weight and total biomass were determined after drying plant tissues (oven 50 ºC for 72 hours). All dried plant tissues were turned into powder. Then the concentration of metal elements in plant samples was determined using ICP-OES based on the method of Salt et al. (1998) and Al-Oud Saud (2003).Metal Accumulation Index (MAI) was calculated using the following formula to determine the amount of metals accumulated in plants. (Liu et al., 2007):  Results and discussionComparison of means showed that urban and industrial wastewater treatments caused significant changes in all examined parameters, including the fresh weight of leaf, root, whole plant, and ramets, dry weight of leaf, length of leaf and roots, the height of plants and ramets, relative leaf water content, leaf gel weight, ratio gel to leaf, total biomass, number of ramets and root TI. The highest index of MAI was observed in plants treated by UWW, and the reduction of all mentioned parameters was more under treatment with UWW than IWW. Under the IWW treatment, all parameters decreased, but the average number of ramets increased compared to the control.Considering that MAI shows the overall performance of plants for co-accumulation of metal elements (Liu et al., 2007), A. vera was successful in accumulating Zn, Cr, Pb, Cu, Mn, Ni, and Mg. Previous studies have reported that plant species with a high MAI value should be used as barriers between contaminated and vulnerable areas, such as parks and residential areas (Nadgorska–Socha et al., 2017). It has been reported that high levels of metals in the soil inhibit various metabolic functions of plants and cause a delay in growth. The toxicity of heavy metals in different plants varies according to factors such as the type of plant, the bioavailability of metals, and the amount of metal displacement in the plant organs (Wang et al., 2006; Usman et al., 2005).The results indicate that an increase in the concentration of heavy metals probably decreases the amount of plant production, the size of the cells, and the dry weight of the organs. (Sharma and Dubey, 2005; Yadollahi et al., 2016). ConclusionAccording to MAI, morphological and physiological characteristics of the A.vera under UWW and IWW treatments, A.vera can be a good refining plant for cultivating and creating a green belt in contaminated soils. Due to the remarkable purifying ability of A.vera in removing heavy metals from contaminated soils, it is recommended to cultivate A.vera in areas polluted with industrial and urban wastewater to prevent the spread of pollution to the surrounding lands.  AcknowledgementThis article is extracted from the results of Sareh Ebrahimi Nokande’s Ph.D. thesis from the Faculty of Sciences, University of Mohaghegh Ardabili, Ardabil, Iran. The authors would like to thank University of Guilan for the technical supports.